Antiques con ebook Trash 'n' treasures mystery series, book 8. - Allan, Barbara (Trash 'n' Treasures Mystery, 2014)
"One of the funniest cozy series going." -- Ellery Queen Mystery Magazine Brandy Borne and her drama-queen mom, Vivian, take their antiques show on the road, for an off-Broadway farce mixing mirth and murder. A world away from small-town Serenity, the ditsy duo--chaperoned by their trusty shih tzu, Sushi--arrive in the Big Apple, blissfully unaware that they will soon cross paths with a rotten-to-the-core killer. As the dynamic dames descend upon a comic-book convention--to sell a rare 1940s Superman drawing--Vivian makes a show of keeping the valuable sketch locked to her wrist in a briefcase. When an intruder breaks into their hotel suite, they naturally suspect a felonious fan, over-eager to acquire their artwork. But this not-so-super villain proves less interested in the Man of Steel than in stealing a man's life, as Brandy and Mother stumble onto a murder victim impaled by a pen-shaped award. Suspects ranging from comic-book collectors to crime kingpins lead Brandy and Mother on a merry madcap Manhattan misadventure, taking them from convention hall to strip joint, from retirement home to precinct lock-up. Has the con been conned by a killer? If so, only Brandy, Mother and Sushi can stop this fatally foul funny-book fiend. Don't miss Brandy Borne's tips on antiques! Praise For Barbara Allan's Trash 'N' Treasures Mysteries! Antiques Chop "The characters shine with brassy humor . . . series fans will applaud." -- Publishers Weekly Antiques Disposal "A humorous cozy that teems with quirky characters." -- Booklist Antiques Knock-Off "Scenes of Midwestern small-town life, informative tidbits about the antiques business, and clever dialog make this essential for those who like unusual amateur sleuths." -- Library Journal Antiques Bizarre "If you delight in the absurd and enjoy manic humor, you'll treasure the Trash 'n' Treasure mysteries." -- Mystery Scene Antiques Flee Market "Lively. . .this bubbly tongue-in-cheek cozy also includes flea market shopping tips and a recipe." -- Publishers Weekly Antiques Maul "Charming. A laugh-out-loud funny mystery." -- Romantic Times Book Reviews (4 stars)